0062 "rotating shift work and metabolic syndrome among employees working in tertiary care hospital in southern india". (21st August 2017) - Alex, Reginald George; Kumar, Santhosh; Kirupakaran, Henry
Abstract : Background: Metabolic syndrome and shift workers are on the rise. There is conflicting evidence whether shift work predisposes to development of metabolic syndrome. Objectives: To study the prevalence of metabolic syndrome among shift and daytime workers in a South Indian hospital and to assess the association between shift work and metabolic syndrome. Methodology: The study had 2 groups: shift and daytime workers between ages 25–50 years. The sample size calculated was 79 in each group to demonstrate 12.5% difference in the prevalence of metabolic syndrome with a power of 80% and α error of 5%. The primary outcome studied was the prevalence of metabolic syndrome and secondary outcomes studied were the odds of developing metabolic syndrome among shift workers. Chi square test was used to measure the difference in the categorical variables; independent student t test for mean difference in the continuous variables. Univariate analysis and multivariable logistic regression were used to test the significance of relevant variables on metabolic syndrome. Results: We studied 80 shift and 80 daytime workers. Baseline characteristics were different for the following parameters: daytime workers were older, had more vegetarians, better sleep and were less physically active. Metabolic syndrome prevalence was 33.1% among the participants. The adjusted odds ratio for the shift workers to develop metabolic syndrome was 0.55 (95% CI 0.24–1.29) with a P value of 0.17. Conclusion: Metabolic syndrome was present in every third person among the study participants and there was no significant association with shift work.